Analysis of the Utilization of Concrete Mat with Different Configuration on Settlement Behaviour of Soft Soil Via PLAXIS 2D - Loo, Jia Yiin; Yusof, Mohd Fairus (Recent Trends in Civil Engineering and Built Environment, 2023)
Problematic soil found along the local coastal plains has low shear strength and high compressibility, causing road failures such as settlement. However, it is often treated in way that the subgrade strength is neglected which causes failure to repeat in an unending cycle. The aim of this study is to model the soft soil improvement using PLAXIS 2D to calculate the vertical settlement and lateral displacement of soft soil when a different configuration of concrete mat is laid and further deduce the best configuration out of it. The configuration of the concrete mat for the analysis is diversified into four categories, material, spacing, shape, and the presence of geotextile. A plane strain condition is adopted and the embankment is assumed to be symmetrical in its cross section. A Hardening Soil (HS) model is used to model the embankment, a Soft Soil (SS) model for the soft soil layer, and a Linear Elastic (LE) model for the concrete mat. The outcome of the simulation has a consistent trend in terms of all the manipulative variables of this study. Shape-wise, the rectangular ConcMatt is preferred over the trapezoidal ConcMatt. Meanwhile, conventional concrete mats are much effective in vertical settlement reduction, but lightweight concrete mats contribute to less lateral displacement at the toe of the embankment. Placing the ConcMatt at 10 mm intervals is preferable to 20 mm intervals because it creates a larger reinforced contact area with the embankment. Geotextiles have a significant contribution to both vertical settlement reduction and lateral displacement reduction. As a result, the rectangular conventional ConcMatt with 10 mm spacing and a layer of geotextile is determined to be the best model set in vertical settlement reduction, while the rectangular lightweight ConcMatt with 10 mm spacing and a layer of geotextile is the best in lateral displacement reduction.